(untitled) (Global Journal of Science Frontier Research, 2021)
Hydroxyapatite (HAp) with the chemical formula of Ca 10 (PO 4 ) 6 (OH) 2 is a mineral component found in bone structure, and has broad application in many fields. Several sources can be used for the extraction of HAp either synthetic or natural. However, sources such as porcine and bovine have drawbacks that decreased the demand of HAp.This study aimed toextract and determine particle size distribution and pore characteristics ofhydroxyapatite nanoparticles (HAp NPs) derived from spotted sardinella (Amblygaster sirm). Further characterization of extracted HAp NPswas carried out by Scanning Electron Microscopy (SEM), Energy Dispersive X-ray Spectroscopy (EDS)and Brunauer-Emmett-Teller(BET).SEM analysis has shown that the extracted HApNPs has an irregular sphere-like shape with particle size distribution ranged from 95nm to 100nm.